'COVID bail': the response of Victorian courts and prisons in navigating the impact of COVID-19. Issue 1 (2nd January 2021) - Greener, Mihal
ABSTRACT: The rapid increase in applications for bail was one of the earliest responses to COVID-19 across the Victorian court system. As the courts addressed the challenges that the pandemic posed it was accepted that COVID-19 would be taken into account as a surrounding circumstance relevant to the determination of bail applications. The consideration of conditions in custody under COVID-19 restrictions as a factor relevant to the determination of bail applications has highlighted the need for greater communication and transparency of the onerous conditions for prisoners under COVID-19 restrictions. While it was established that the impact of the pandemic on those in custody would be assessed by the courts on a case by case basis, the paucity of information on lockdown conditions within Victorian prisons has impeded the court's ability to assess the competing considerations before it in determining questions of bail.